PENGARUH DEBT TO EQUITY RATIO (DER), TOTAL ASSET TURNOVER (TATO), DAN CURRENT RATIO (CR) TERHADAP HARGA SAHAM DENGAN RETURN ON EQUITY (ROE) SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BEI PERIODE 2022-2024 - Nadiah Silviana; Ika Wahyuni; Ida Subaida (Jurnal Mahasiswa Entrepreneurship (JME), 2026)
The capital market plays a crucial role as an investment platform for investors and a source of funding for companies, particularly those listed on the LQ45 index, known for their liquidity and strong performance. This research was conducted with the aim of analyzing the influence of Debt to Equity Ratio, Total Asset Turnover, and Current Ratio on stock prices, with Return on Equity as an intevening variable. The approach used in this study is quantitative descriptive. The population of this study includes companies listed in the LQ45 index of the Indonesia Stock Exchange for the period 2022–2024, using a purposive sampling technique. For data analysis, the method used was Partial Least Squares – Structural Equation Modeling (PLS-SEM) using the Smart PLS 3.0 application. The results show that Debt to Equity Ratio and Total Asset Turnover show a positive but insignificant effect on Return on Equity, while the Current Ratio shows a negative but insignificant effect on Return on Equity. On the other hand, Debt to Equity Ratio and Total Asset Turnover have a significant negative effect on stock prices, while Current Ratio and Return on Equity show a positive but insignificant effect on stock prices. In the indirect effect test, Debt to Equity Ratio and Total Asset Turnover have a positive but insignificant effect on stock prices through Return on Equity, while Current Ratio shows a negative but insignificant effect on stock prices through Return on Equity.